2022
DOI: 10.3390/vaccines10070990
|View full text |Cite
|
Sign up to set email alerts
|

How Vaccinations Changed the Outcome of COVID-19 Infections in Kidney Transplant Patients: Single-Center Experience

Abstract: Kidney transplant recipients are a vulnerable population at risk of a life-threatening COVID-19 infection with an incidence of death four-times higher than in the general population. The availability of mRNA COVID-19 vaccines has dramatically changed the fate of this infection also within this fragile population. Transplanted patients have an impaired immunological response also to mRNA vaccines. In March 2021, however, we started a vaccination campaign. These preliminary results show that both the incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Our data also showed that vaccine response in KTR-VACCs was strongly influenced by increased age, decreased renal function, antimetabolite maintenance therapy and time from transplantation. The importance of age in mRNA-vaccine response was also described by Grupper et al, who showed the influence of age on mRNA-vaccine response in dialysis patients regardless of chronic medical conditions [ 5 ] and Campise et al, who reported older age and dyspnea as variables associated with an increased risk of hospitalization [ 28 ]. Moreover, persistent but declining anti-SARS-CoV-2 humoral immunity six months after the three-dose vaccination schedule with BNT162b2 in healthy individuals was more pronounced among older people [ 29 ].…”
Section: Discussionmentioning
confidence: 82%
“…Our data also showed that vaccine response in KTR-VACCs was strongly influenced by increased age, decreased renal function, antimetabolite maintenance therapy and time from transplantation. The importance of age in mRNA-vaccine response was also described by Grupper et al, who showed the influence of age on mRNA-vaccine response in dialysis patients regardless of chronic medical conditions [ 5 ] and Campise et al, who reported older age and dyspnea as variables associated with an increased risk of hospitalization [ 28 ]. Moreover, persistent but declining anti-SARS-CoV-2 humoral immunity six months after the three-dose vaccination schedule with BNT162b2 in healthy individuals was more pronounced among older people [ 29 ].…”
Section: Discussionmentioning
confidence: 82%